Onset and duration of transient infections among antibody-diverse beef calves exposed to a bovine viral diarrhea virus persistently infected calf - Nickell, Jason S.; White, Bradley J.; Larson, Robert L.; Renter, David G.; Roque, Julia; Hesse, Richard A.; Oberst, Richard D.; Peddireddi, Lalitha; Anderson, Gary Allen (My University, 2012)
Persistently infected (PI) cattle are the reservoir of bovine viral diarrhea virus (BVDV), yet data describing BVDV transient infections (TI) among non-PI populations are minimal. Study objectives consisted of: 1. Estimating the onset and duration of TI based on serum VI and rRT-PCR, and 2. Determination of the potential of TI cattle to shed BVDV. Two 21-day studies were performed where one PI calf was commingled with a confirmed non-PI cattle population with heterogeneous BVDV antibody status (n=12 and n=15, respectively). After PI exposure, virus isolation on serum and nasal swabs failed to detect BVDV among non-PI cattle. Despite minimal disease (n=1), BVDV transmission occurred as 78% (n=21) of non-PI calves displayed a four-fold rise in BVDV antibody titers, 81.5% (n=22) displayed a transient positive serum BVDV rRT-PCR outcome, and 74.1% (n=20) displayed a transient positive rRT-PCR result on nasal swabs. Median days of positive serum rRT-PCR onset and duration were 10.0 (range: 6-21) and 3.0 (range: 1-9) days, respectively. These data suggest that non-PI cattle can become TI with minimal clinical disease while possessing the potential to transmit BVDV. The speed with which exposed cattle become transiently infected and their potential ability to shed the virus may impact design and implementation of BVDV control programs.
Keywords: Bovine viral diarrhea virus; Cattle; Transient/acute infection